Effects of Prebiotic Fiber Xylooligosaccharide in Adenine‐Induced Nephropathy in Mice. Issue 15 (2nd July 2018) - Yang, Jieping; Li, Qing; Henning, Susanne M.; Zhong, Jin; Hsu, Mark; Lee, Rupo; Long, Jianfeng; Chan, Brenda; Nagami, Glenn T.; Heber, David; Li, Zhaoping
Abstract : Scope: This study evaluates the effect of the prebiotic fiber xylooligosaccharide (XOS) on kidney function and gut microbiome in mice with adenine‐induced chronic kidney disease (CKD). Method and results: Mice are fed the control diet containing adenine for 3 weeks to induce CKD and are switched to XOS supplemented (2 or 7%) or control diets for another 3 weeks. Mice with CKD exhibit increased blood urea nitrogen (BUN), creatinine, and kidney histopathology. XOS significantly reverses kidney injuries in CKD mice. Analysis of cecum microbiota reveales that adenine‐induced CKD does not change alpha diversity, and XOS induces a decrease of alpha diversity in control mice and mice with CKD. Beta diversity analysis shows significant clustering according to experimental groups. Six out of the nine bacterial genera enriched in CKD are significantly reduced with XOS intervention. Furthermore, XOS increases cecal short‐chain fatty acid (SCFA) production in both control and CKD mice. Cecal SCFAs and blood propionate are negatively correlated with BUN. XOS also decreases blood p‐cresol sulfate in CKD mice, likely resulting from altered microbial tyrosine metabolism. Conclusion: These results show that XOS intervention improves kidney function in mice with CKD, and is associated with profound changes in microbial composition and metabolism. Abstract : Xylooligosaccharide (XOS) is considered a prebiotic fiber . This study provides evidence that dietary XOS supplementation is effective in enhancing recovery from adenine‐induced kidney damage by decreasing fibrosis and inflammation, as well as lowering circulating uremic toxin p‐cresol sulfate through regulating the gut microbiome.